Risk of anaemia with long-term metformin use in a community setting - Donnelly, L; Gardner, K; Coleman, R; Sattar, N; Hattersley, A; Holman, R; Pearson, E (Springer, 2017)
The DPP Outcomes Study showed that metformin use in individuals with impaired glucose tolerance was associated with increased risk of anaemia at 5 years, independent of vitamin B12 status. In people with type 2 diabetes (T2D), anaemia is a common finding but the impact of long-term metformin use on anaemia risk has not been studied. We examined whether cumulative exposure to metformin in T2D is associated with an increased risk of anaemia using data from a large population-based cohort containing longitudinal prescribing and repeated haematology measures.